2009
DOI: 10.1063/1.3275727
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical assembly of light-emitting polymer nanofibers in helical morphologies

Abstract: Published by the AIP PublishingArticles you may be interested in Temperature-dependent electroluminescence spectra of poly(phenylene-vinylene) derivatives-based polymer light-emitting diodes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…More reproducible methods to generate fibers into well-defined arrays with hierarchical structures are needed [191]. As these electrospinning techniques are perfected, and through interdisciplinary collaborations, electrospinning is expected to become more significant in the fields of nanotechnology and bioengineering [143]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More reproducible methods to generate fibers into well-defined arrays with hierarchical structures are needed [191]. As these electrospinning techniques are perfected, and through interdisciplinary collaborations, electrospinning is expected to become more significant in the fields of nanotechnology and bioengineering [143]. …”
Section: Discussionmentioning
confidence: 99%
“…A tilted glass slide was used as the collector and it was found that tilt angles greater than 45° did not result in helical fibers [142]. Helical light-emitting conjugated polymers in which the polymer molecular weight affects the loop size and corresponding color shift have also been fabricated using the electrospinning technique [143]. The fibers with the most stretched helical geometries were formed from polymer solutions with the highest molecular weights.…”
Section: Helicalmentioning
confidence: 99%
“…This can be attributed to the stretching of the liquid jet which can favor a more extended conformation of the backbones, as also confirmed by observed longer PL lifetimes 54. Emission spectra are typically comparable to spin‐cast films, or display a small blue‐shift 31, 84. These effects can be related to changes in the nanoscale environment that can perturb the local refractive index (particularly in fibers fabricated by blending conjugated molecules with inert polymers), and to suppression of exciton migration toward sites of lower energy.…”
Section: Applications Of Active Nanofibersmentioning
confidence: 64%
“…These effects can be related to changes in the nanoscale environment that can perturb the local refractive index (particularly in fibers fabricated by blending conjugated molecules with inert polymers), and to suppression of exciton migration toward sites of lower energy. Moreover, self‐absorption within the organic material and scattering effects can significantly modify the shape of the emitted spectra, thus determining a rich observable phenomenology 84–87…”
Section: Applications Of Active Nanofibersmentioning
confidence: 99%
“…ES has emerged as a successful method to pattern various types of polymeric nanofibers on a large scale [29], and has applications in the fields of sensors and actuators [30][31][32][33], energy storage [34,35], smart textiles [36][37][38][39], optoelectronics [40,41], tissue engineering [42][43][44][45], prosthetics [46], drug delivery [47,48], microresonators [49], and piezoelectric energy generators [50]. Just like in DPL, in ES a material is deposited on a surface from an ink solution.…”
Section: Electrospinningmentioning
confidence: 99%